Towards a framework for assessing the sustainability of social-ecological landscapes - Atampugre, Gerald; Mensah, E.; Mabhaudhi, Tafadzwanashe; Cofie, Olufunke O. (CGIAR Initiative on West and Central African Food Systems Transformation, 2022)
The report proposes a framework for assessing the sustainability of social-ecological landscapes (SEL) to be used by the West and Central African Food Systems Transformation (TAFS-WCA) initiative for research, planning, and implementation of its Work Package 3 (WP3). It builds on existing assessment frameworks from relevant fields (e.g., Eco agriculture, Agroecology, Integrated Landscape Management, etc.). At the center of a Sustainable Social-Ecological Landscape (SSEL) is the improvement of the management of land and the natural resource base in such a way that land use concurrently meets three goals: (i) provision of products (e.g., food) and services on a sustainable basis, (ii) support for sustainable livelihoods for all social groups and (iii) conservation of the full complement of biodiversity and ecosystem services. Globally, SSEL related approaches like eco-agriculture, agroecology, and landscape approaches are already being applied, with promising results, especially in places where food production, poverty alleviation, and conservation of biodiversity, water, and ecosystem services are all high priorities. However, a comprehensive framework for measuring/monitoring landscape status and performance vis-a-vis competing landscape uses and management interventions has not been given much priority in the literature. Different forms of land use, such as forestry, agriculture, extraction of minerals, conservation/protected areas, and settlements, are interdependent. Therefore, landscape performance and monitoring frameworks that focus exclusively on protecting natural resources or the intensification of agriculture and other land uses can only give an incomplete viewpoint/overview of landscapes with all their uses and stakeholders. Considering the SSEL goals above, a holistic conceptual framework for landscape-based assessment is needed; such a framework must consider the drivers and effects of land use and the individual management interventions as well as the complex interactions among different land uses and interventions across the landscape. The present study proposes the Drivers-Pressure-State-Impact-Response (DPSIR) framework for SEL. It is important to emphasize that this study recognizes that different individuals and organizations under the TAFS-WCA initiative may have different interests in understanding the status and performance of selected SELs. The research envisages two important applications of a framework for measuring and understanding SEL: i) it can facilitate inclusive decision-making by multiple stakeholders working in the same landscape by explaining interactions, synergies, and trade-offs among SSEL goals and landscape components, and ii) when SSEL-related management innovations are successful (or otherwise), the framework can help document the same, reinforcing the case for adopting and scaling up innovations.